Chemical Gardens Under Mars Conditions: Imaging Chemical Garden Growth In Situ in an Environmental Scanning Electron Microscope. Issue 10 (12th May 2021) - Sainz‐Díaz, C. Ignacio; Escribano, Bruno; Sánchez‐Almazo, Isabel; Cartwright, Julyan H. E.
Abstract: We have performed and visualized chemical garden growth experiments directly in situ in an environmental scanning electron microscope. The microscope chamber simulates the surface of Mars. We demonstrate that chemical gardens can form under the conditions of temperature and pressure existing on Mars in the presence of liquid water, silicates, and metal salts. Using chemical gardens from aluminum salts, tubes were formed where the external surface is formed principally by silicate and the inner surface is predominantly aluminum oxide‐hydroxide. It should thus be expected that similar growths of metal salts may be found in geological explorations of water‐rich environments during the search for life on Mars. Plain Language Summary: Mars today is a desert planet with scarcely any water, but we know that it used to have much more. So the search for life on Mars now is a search for water in the desert, and the search for fossil life is a search for places where there used to be water. We show with experiments in an environmental scanning electron microscope that chemical gardens should form on Mars under these conditions. It is important to be aware of this so as not to fall into the trap of thinking that these lifelike forms are fossils, but also important because on Earth, so perhaps on Mars too, chemical gardens may be where life was incubated. Key Points: We have performed and visualized chemical garden growth experiments directly in situ in an environmental scanning electron microscope We demonstrate that chemical gardens can form under the conditions of temperature and pressure existing on Mars Similar growths of metal salts may be found in geological explorations of water‐rich environments during the search for life on Mars